Clinical and ultrasound variables for early diagnosis of septic acute kidney injury in bitches with pyometra - Gasser, Beatriz [UNESP]; Ramirez Uscategui, Ricardo Andres; Maronezi, Marjury Cristina [UNESP]; Pavan, Leticia [UNESP]; Rodrigues Simoes, Ana Paula [UNESP]; Martinato, Fernanda [UNESP]; Silva, Priscila [UNESP]; Crivellenti, Leandro Zuccolotto; Rossi Feliciano, Marcus Antonio (Nature Publishing Group, 2020)
The aetiology of septic acute kidney injury (AKI) is not completely elucidated. Early identification of AKI in septic patients is considered to improve survival rate since it allows rapid treatment onset. We evaluated clinical, haematological, urinary, B-mode, spectral Doppler, and contrast-enhanced ultrasound variables in 20 bitches with pyometra as sepsis models and 12 healthy controls. All animals with pyometra presented some degree of renal damage on histological examination; however, sequential organ failure assessment (SOFA) classified only 40% cases with sepsis. AKI derived from systemic infection was identified in 57% of cases with hypoperfusion and in 22% with inflammation, being an affection of multifactorial origin. Among the evaluated parameters, urinary protein/creatinine ratio >0.15, serum albumin <2.94mg/dL, time-averaged minimum velocity <21.5cm/s, renal length/aorta diameter ratio >5.93, pulsatility index >1.53, haematocrit <45%, time-averaged maximum velocity <45.7cm/s, haemoglobin <16g/dL, leukocytes >12.53 x 10(3)/uL, and cortical contrast peak intensity <69%, in the order of accuracy, are significant indicators of septic AKI with an accuracy >80%. Thus, AKI is a very prevalent condition in septic patients, derived mainly from changes in renal perfusion and inflammation. Additionally, reviewing the SOFA score parameters is suggested to identify renal failure.